LINGUISTIC PATHWAYS TO NATIONALISM: A STUDY OF IDENTITY AND RESISTANCE IN SELECTIVE NOVELS OF R. K. NARAYAN - Krishna, Kota Sai; Madhavi, P. Asha; Seshagiri, H (ShodhKosh: Journal of Visual and Performing Arts, 2022)
This study examines the theme of nationalism in R. K. Narayan’s novels—Waiting for the Mahatma, Swami and Friends, The Guide, and The Man-Eater of Malgudi—through a linguistic lens. By analysing dialogues, character interactions, and symbolic elements, the research explores how Narayan employs language to encapsulate the complexities of Indian nationalism in both colonial and postcolonial contexts. Narayan’s nuanced portrayal reveals nationalism as a multifaceted phenomenon, deeply rooted in personal growth, cultural preservation, and collective resilience. Characters such as Bharati, Swaminathan, Raju, and Nataraj reflect different facets of nationalist sentiment, from pragmatic commitment to instinctive defiance and self-sacrifice. The linguistic analysis demonstrates how Narayan’s characters use language to navigate the tensions between tradition and modernity, individual autonomy and collective identity, and colonial resistance and cultural renewal. By examining tone, diction, and rhetorical devices, the study highlights how Narayan transforms personal narratives into broader reflections of Indian cultural pride and resilience. This research underscores the role of literature in articulating national identity, positioning Narayan’s works as enduring contributions to the discourse on Indian nationalism. Through his unique narrative style, Narayan captures the evolving spirit of nationalism, offering insights that remain relevant within postcolonial and cultural studies.